GE_GERICHTE P/24772/2019 vom 18. März 2020 - GE Cour de justice (2020)
ABUS DE CONFIANCE;MÉNAGE COMMUN;SOUPÇON;ESCROQUERIE;DROIT D'ÊTRE ENTENDU | CPP.310.al1.leta; CP.180; CP.146.al3; CP.138.al3.ch1; Cst.29.al2